An Unexpected Case Report of Adrenal Lymphangioma: Mimicking Metastatic Tumor on Imaging in a Patient With Pancreatic Cancer - Wan, Shang; Liu, Xijiao; Tian, Bole; Cao, Dan; Li, Mao; He, Yuhao; Song, Bin (Frontiers in Endocrinology, 2021)
Adrenal lymphangioma is a very rare benign lesion worldwide and remains challenging for early diagnosis, especially when the patient has some complicated clinical disease. This is an unusual case of a 68-year-old man who was admitted to our hospital with a history of pancreatic tumor. Computed tomography (CT) images and subsequent magnetic resonance imaging (MRI) revealed a mass located in the left adrenal gland, presenting a similar enhancement pattern of the pancreatic tumor, and according to the imaging features, the patient was suspected to have an adrenal metastatic tumor originating from the pancreatic tumor. The patient underwent a surgical resection of the pancreatic tumor and the left adrenal gland. The pathologic diagnosis proved to be lymphangioma deriving from the left adrenal gland. This is the first report presenting an adrenal lymphangioma mimicking a metastatic tumor of pancreatic origin, which brings us a new insight for the differential diagnosis of the adrenal lesion, especially when patient has a particular medical history. As we know, imaging examination is helpful for accurate preoperative diagnosis; however, the diagnosis of malignant tumor solely based on imaging procedures should be made cautiously by radiologists.